2008
DOI: 10.1110/ps.036103.108
|View full text |Cite
|
Sign up to set email alerts
|

Tissue transglutaminase modulates α‐synuclein oligomerization

Abstract: We have studied the interaction of the enzyme tissue transglutaminase (tTG), catalyzing cross-link formation between protein-bound glutamine residues and primary amines, with Parkinson's diseaseassociated a-synuclein protein variants at physiologically relevant concentrations. We have, for the first time, determined binding affinities of tTG for wild-type and mutant a-synucleins using surface plasmon resonance approaches, revealing high-affinity nanomolar equilibrium dissociation constants. Nanomolar tTG conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 22 publications
7
48
0
Order By: Relevance
“…As presented in Fig. 1D, the NMR spectra of ␣-syn obtained for the two different purification procedures are nearly identical, and both clearly indicate the highly disordered conformational ensemble that was originally documented (23) and has since been extensively studied by us (39 -46) and many other groups (47)(48)(49)(50)(51)(52)(53).…”
Section: Resultsmentioning
confidence: 57%
“…As presented in Fig. 1D, the NMR spectra of ␣-syn obtained for the two different purification procedures are nearly identical, and both clearly indicate the highly disordered conformational ensemble that was originally documented (23) and has since been extensively studied by us (39 -46) and many other groups (47)(48)(49)(50)(51)(52)(53).…”
Section: Resultsmentioning
confidence: 57%
“…235), mechanistic studies in TG2-modified animals, aimed at evaluating the role of TG2 in these diseases, have not yet been undertaken. Recent studies suggest that TG2-mediated intraand intermolecular cross-linked ␣-synuclein is unable to form the cytotoxic, structured fibrillar aggregates responsible for neural membrane disruption in Parkinson's disease (247). TG2-mediated cross-linking may, thus, prevent progression of Parkinson's disease.…”
Section: J Neurodegenerative Disordersmentioning
confidence: 99%
“…However, although all these studies suggest the possible involvement of the TGs in the formation of deposits of protein aggregates in neurodegenerative diseases, they do not indicate whether aberrant TG activity per se directly determines the disease progression. For example, several experimental findings reported that TG2 activity in vitro leads to the formation of soluble aggregates of a-synuclein [47] or polyQ proteins [48,49] . To date, as previously reported, at least ten human CAG-expansion diseases have been described (Table 2) [50][51][52][53][54][55][56][57][58][59] and in at least eight of them their neuropathology is caused by the expansion in the number of residues in the polyglutamine domain to a value beyond [35][36][37][38][39][40].…”
Section: Role Of the Transglutaminases In Neurodegenerative Diseasesmentioning
confidence: 99%